Correcting Icelandic Manuscripts in the Second Half of the Fourteenth Century - Lea D. Pokorny (Scripta Islandica)
Writing is a task prone to errors and mistakes. While modern devices allow for invisible corrections, medieval scribes often had to use methods that would remain visible to a manuscript’s future users. Previous studies on Western European manuscripts indicate that these methods can be indicative of the people responsible as well as the time of correction, thus revealing important information about the book production process. Yet, corrections in Icelandic manuscripts have hitherto not found much scholarly attention.